(untitled) (BSAA arte, 2019)
This article offers a new focus on the almost forgotten figure of the architect, politician and businessman Félix Ribas y Solá (1797-1864), a prominent personality in Barcelona during the reign of Isabel II and architect to the Universidad Literaria for twenty years. Analysed here are his project for the remodelling of the former convent of the Shod Carmelites as the headquarters of the Universidad Literaria (1840), and another project for a new building that he considered erecting on the same site (1853-1854).